2018
DOI: 10.3389/fmars.2018.00111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mg and Ca on the Stability of the MRI Contrast Agent Gd–DTPA in Seawater

Abstract: Gadolinium diethylenetriaminepentaacetic acid (Gd-DTPA) is widely applied as a contrast enhancer in medical MRI. As Gd-DTPA is only minimally captured in wastewater treatment plants (WTPs) or degraded by UV light and other oxidative processes, concentrations in rivers have increased globally by orders of magnitude following its introduction in 1987. The complex also seems impervious to estuarine scavenging and is beginning to emerge in coastal waters, yet it is unknown how its stability is changed by competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…This suggests that the samples are roughly of the same age, as it has been shown that there is a degradation of the complexes over time (Holzbecher et al, 2005). Several factors have been found to influence the destabilization of Gd-complexes e.g., transmetallation or competition for binding places of the DPTA complexes by Ca, Mg, or K ions (Schijf and Christy, 2018).…”
Section: Effect Of Uv/h 2 O 2 Treatment On Measured Anthropogenic Gd mentioning
confidence: 76%
See 1 more Smart Citation
“…This suggests that the samples are roughly of the same age, as it has been shown that there is a degradation of the complexes over time (Holzbecher et al, 2005). Several factors have been found to influence the destabilization of Gd-complexes e.g., transmetallation or competition for binding places of the DPTA complexes by Ca, Mg, or K ions (Schijf and Christy, 2018).…”
Section: Effect Of Uv/h 2 O 2 Treatment On Measured Anthropogenic Gd mentioning
confidence: 76%
“…However, the authors suggested that different biogeochemical conditions in natural waters (e.g., different concentrations of organic matter) potentially influence the degradation of Gd complexes (Holzbecher et al, 2005). In estuaries, up to 15% of Gd-DPTA can dissociate due to the competition of Mg or Ca ions for DTPA (Schijf and Christy, 2018). Yet, because of the many different complexes in use, their stability may differ under natural conditions and little is known about degradation and transformation of the complexes under natural conditions (Birka et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The situation is different in the sea, but few data exist on the stability of GBCAs in marine waters. At present, only gadopentetate dimeglumine has been studied in depth 26 . This contrast agent is substantially dissociated upon mixing of river water with seawater in estuaries.…”
Section: Resultsmentioning
confidence: 99%
“…Speciation analysis of the different stages of wastewater treatment shows samples after the biological treatment stage and effluent contain unidentifiable Gd species, suggesting that species transformation had occurred 46 . It is understood that degradation of the Gd‐chelate complex is possible from bacterial attack, UV photo‐oxidation, as well as transmetallation 48 . Models 48 demonstrate that the stability of Gd DTPA complexes are about six orders of magnitude lower in saltwater than in freshwater due to substantial transmetallation competition from abundant magnesium and calcium.…”
Section: Species Transformationmentioning
confidence: 99%
“…It is understood that degradation of the Gd‐chelate complex is possible from bacterial attack, UV photo‐oxidation, as well as transmetallation 48 . Models 48 demonstrate that the stability of Gd DTPA complexes are about six orders of magnitude lower in saltwater than in freshwater due to substantial transmetallation competition from abundant magnesium and calcium. This suggests that upon mixing of river water with seawater in estuaries, up to 15% Gd can be released from the DTPA ligand due to transmetallation competition from Mg and Ca alone, as modeled with marine water samples from Hatje et al 48 …”
Section: Species Transformationmentioning
confidence: 99%